Potential environmental impacts from cropping-pattern and land-use changes under Thailand's ethanol production mandate - Suksawat, Jakrapun, author; Graff, Gregory D., advisor; Hoag, Dana L. K., committee member; Loomis, John B., committee member; Paustian, Keith, committee member (Colorado State University. Libraries, 2015)
The primary energy source meeting demand in Thailand is oil, especially in the transportation sector, which has resulted in energy import dependency and environmental impacts (Energy Policy and Planning Office, 2012). To reduce energy import and carbon emission the Thai government has announced a plan, known as “Low Carbon Society” policy that promoted bioenergy use (Ministry of Energy, 2012). The main bioenergy strategy of the Thai government is promotion of ethanol production. Ethanol production targets have been set at 3.0, 6.2, and 9.0 million liters per day, in 2008-2011, 2012-2016, and 2017-2022, respectively (Ministry of Energy, 2012). The main feedstocks for ethanol production in Thailand are cassava and molasses, a by-product from refining cane sugar. The cultivation areas of these energy crops are thus expected to increase and intensify due to expansion on ethanol production. In 2010, it was estimated that 1.61 million tonnes of cassava and 2.19 million tonnes of molasses could serve as feedstock for ethanol production of 2.25 million liters per day. Based on licensed ethanol plants and the ethanol production target for 2022, demand for cassava and molasses from the Thai ethanol industry would increase up to at least 14.34 and 3.96 million tonnes per year. While the current molasses production could serve this feedstock demand, the enormous increase in demand for cassava would significantly increase land-use for cassava cultivation. The ethanol production has been promoted for the purpose of energy security, GHG emission reduction, and economic development. However, it is unclear that the ethanol target of the Thai government is possible in both economic and political terms regardless of the cropping land-use change and thus the environmental impacts. Moreover, the planning, monitoring, and setting suitable cultivation area for ethanol feedstock could help to reduce its negative impact on land use change, deforestation, and biodiversity loss (Scarlat and Dallemand, 2011). This proposed study thus focuses on three interrelated topics: the economic and political feasibility of enacting these mandates; the potential cropping land-use change under realistic scenarios; and the potential environmental impacts of these changes. The objectives for each of these are as follow: 1. To evaluate the current economic and political feasibility to produce nine million liters per day of ethanol. The economic feasibility regards to estimate adequacy of ethanol feedstock crops and cultivate areas as compared to other major competing crops benefit. The political feasibility issues regards the competition of interests among influential parties that play important roles in the Thai energy and agricultural industries, such as the government itself, oil companies, and farmer associations. 2. To assess on the outcome of cropping land-use change when ethanol target is introduced. The significant increase in ethanol and feedstock demand is expected to dramatically alter crop cultivation areas. Moreover, energy crops and competitive crop prices would also impact on farmers’ decision. Thus, individual farmers’ economic decision when adopting ethanol feedstock crops to be cultivated instead of other competitive crops will be investigated. Various scenarios cropping land-use change when ethanol mandate is implemented and subsequent will be studied in-depth by using the Multi-criteria Analysis and Geographic Information Systems (GIS). 3. To estimate the environmental impacts of Thai ethanol mandate under these various scenarios. Ethanol mandate implementation does not only directly affect GHG reduction, but also effects GHG balance due to cropping land-use change. Other environmental impact such biodiversity can also be measured. Based on a range of realistic alternative scenarios of cropping land-use change, the range of impacts on several measures of environmental quality will be estimated. The CENTURY model will be used to account soil carbon sequestration as GHG balance. Meanwhile, the nitrous oxide, methane, and biodiversity loss from cropping land-use change are discussed.
Keywords: century model; GIS; land-use change; ethanol policy; biofuel; greenhouse gas emissions